Strategies for Educating Deaf and Hard-of-Hearing Learners in Lesotho: A Literature Review - Morai, Mamotjoka Joyce; Kawai, Norimune (Angstrom Centre of Education, 2025)
Exploring research about teachers’ instructional strategies and challenges can help reveal potential opportunities to improve the quality of education iterated by the United Nations Sustainable Development Goal 4 (SDG 4). This review summarizes the literature on the strategies used to teach deaf and hard-of-hearing learners (DHHLs) in Lesotho, the rationale behind using the strategies, and the challenges teachers face during instruction. The review involved thoroughly searching, identifying, reading, and summarizing research from databases such as Google Scholar, ResearchGate, and African-related databases. The results indicate a need for further research, as only a few studies have been identified (n=6). A review of these studies indicates an overall need for teacher training to provide more strategies for teachers to enhance instruction for DHHLs. The strategies teachers use are reported to be varied, such as experiments, peer tutoring, demonstrations, bubble maps, and repetition. This variation prompts further examination of factors other than strategies, such as DHHLs’ language backgrounds, to provide more insight into research and practice in addressing their needs.